Evolutionary game analysis of the longitudinal integration of electronic health record based on prospect theory - Xinqi Hu; Ruina Wang; Yuanyuan Wei; Hongwei Lin; Xiaomiao Gui (Scientific Reports)
Abstract Based on the premise of bounded rationality, this study introduces the value function and decision weight function from prospect theory into the framework of evolutionary game theory to analyze the decision-making process of healthcare institutions, patients, and the government during the vertical integration of electronic health records. The study incorporates factors such as loss aversion, sensitivity to gains and losses, and the degree of awareness and utilization of records, to explain the behavioral tendencies of the three players from the perspective of perceived value. It uses simulations to reveal how factors such as the loss aversion coefficient and sensitivity to perceived value influence the evolutionary outcomes. This research extends the discussion of psychological factors, such as risk attitudes and gain-loss perception, in the context of the vertical integration of electronic health record. The findings indicate that: (1) increasing the initial willingness of all parties to participate is a key factor in encouraging active involvement in the EHR integration process; (2) the value of record awareness and the closeness of medical alliances significantly affect participation behavior, thus accelerating the integration process; (3) factors such as loss aversion, sensitivity to gains and losses, and efficacy loss sensitivity have complex effects on the system’s evolutionary path. Policymakers need to consider the risk perception characteristics of all parties and adjust policies accordingly to promote the stable development of the system.